OPTIMIZING CONSTRUCTION PROJECT LIFESPAN VALUE USING TOTAL QUALITY MANAGEMENT PRINCIPLES - El-Messiery, Ramy; Elsherbiny, Emad; Nasr Eldin, Tarek (Journal of Applied Engineering Science, 2024)
An effective strategy aligning costs and quality is pivotal for augmenting project value in the construction industry. This study develops and applies a model to evaluate the impact of Total Quality Management (TQM) principles on Egyptian construction projects. Objectives include identifying key TQM principles, quantifying their value, and validating outcomes through a case study. Methodologically, a TQM evaluation model, utilizing the Relative Importance Index (RII) method and validated via Cronbach’s alpha, is formulated. A value formula estimates the financial impact of top TQM principles compared to construction project life cycle costs. Applied to a 2023 Egyptian construction project case study, the formula demonstrates cost savings surpassing the required investment. Specifically, project value improved 2.77 times using the created Value Engineering Business Approach (VEBA) formula, translating to an estimated 12.8% reduction in total life cycle costs. This research advocates a data-driven approach to prioritize TQM principles, showcasing positive financial returns for firms and endorsing TQM as an effective framework for the Egyptian construction sector.
Keywords: life cycle cost analysis, quality evaluation, total quality management, value analysis, value engineering, value engineering business approach